Penatalaksanaan Recurrent Aphtous Stomatitis Minor pada Pasien Anemia : Laporan Kasus - Maheswari, Larissa Pratama; Yuletnawati, SE (Bhakta Dental Journal, 2025)
Background: Recurrent Apthous Stomatitis (RAS) is an inflammatory condition of the oral cavity characterized by ulcerated lesions commonly found in children and adults. This lesion is one of the oral lesions that often becomes a complaint due to the pain that appears. Case report: A 19-year-old female patient complained of painful ulcer. The complaint was felt 7 days ago, the complaint was on the mucosa of the lower left lip and the mucosa of the cheek on the right. The complaint often appears, comes and goes and recurs since the patient was a teenager. The results of the intraoral examination showed a painful white ulcer, surrounded by redness, unilateral, on the mucosa of the lip at the left corner. On the mucosa of the left cheek there was an painful ulcer, yellowish white surrounded by redness, unilateral, and symptomatic. Discussion: The results of the patient's complete blood count showed that the patient had microcytic anemia. Microcytic anemia is a common type of anemia. Microcytic anemia is characterized by circulating red blood cells that are smaller than normal due to decreased hemoglobin production. Conclusion: Minor RAS is the most common form, affecting approximately 85% of RAS patients. RAS therapy aims to control pain, shorten the duration of existing lesions, and eliminate new lesions. Treatment in this case involves administering topical corticosteroids and iron supplements.